ULOMMA: a maternidade como vivência de reencantamento pelo sagrado no conto de matriz afro-brasileira - Silva, Maria Rodrigues da (2010)
This thesis aims at analyzing motherhood as the living of re-enchantment by the sacred, in an African-Brazilian root tale for children and youth , and confront the emptiness relegated to women in the history of humanity, especially black women, seen as element of breeding to increase male power. To analyze the corpus of this research, many paths were gone through, for dealing with an African-Brazilian root literature, since both in schools as in the public and private libraries have failed to incorporate this literature in their collections. After several searches in libraries, reading rooms, tallow cultural fairs and book publishers, some books by African descent writers were found, among which was the tale Ulomma: the house of beauty, which tells the story of motherhood a black woman. Then the corpus of this research was addresse d exactly about the re-enchantment of the sacredness of motherhood. The adopted methodology followed in the direction of qualitative, critical aproach and analysis of content. To compose the theoretical framework were discussed classical and contemporary authors, in several areas of knowledge, since the object of study, interweave interdisciplinary dialogues among Literature, History, Religion and Education, in a perspective to help combat racism, and to contribute to increase the visibility of black women in the history of mankind. The achieved results in this study point to the need to include more and more, at schools, the African-Brazilian root literature for children and youth in order to deconstruct old stereotypes and racial prejudices. Therefore, this research suggests clues that other studies address this rich literatu re in lessons and open spaces for the re-enchantment of the sacred rite of passage to motherhood.